The child psychology at the beginning of the twenty first century. Impact of the ideological/cultural factors in North America. Repercussions in Peru - Lequerica Durand, Martha (1998)
The purpose of this paper is to analize the impact the Civil Rights Movement, feminism and the War Against Poverty have had on the evolution and reshaping of child psychology in the United States, during the last four decades. These three ideological/cultural factors have played a major role in child/ rearing, education and conceptualization of the child's moral and sex role development as well as in intelligence measurement/assessment, placement in special classes and the dissemination of bilingualism as a tool for teaching. How to apply a similar analysis to the study of child psychology in Latin America and more specifically in Perú, is proposed and recommended.